Association between body image dissatisfaction and body anthropometric indices among Chinese children and adolescents at different developmental stages - Wang, Yuanyuan; Cao, Ruiyao; Peng, Xingwang; Zhang, Li; Zhang, Zizhe; Fu, Lianguo (Frontiers in Public Health, 2022)
Objective: Children at different developmental stages show different physical development and psychological cognitive characteristics and may pay different attention to body parts. The purpose of this study was to analyze the associations between body image dissatisfaction (BID) and body anthropometric indices (BAIs) among Chinese children and adolescents at different developmental stages. Methods: A total of 609 Chinese primary and secondary school students aged 8-15 years (329 boys and 280 girls) were selected using stratified cluster sampling. The students’ body height, sitting height (SH), weight, chest circumference (CC), hip circumference (HC), waist circumference (WC), scapular skinfold thickness (SST), triceps skinfold thickness (TST), and abdominal skinfold thickness (AST) were measured. Boys’ testicular volumes and first spermatorrhea and girls’ breast measures and menarche were assessed using the Tanner stage standard. A body shape questionnaire (BSQ) was used to survey the subject’s BID. Results: In boys with testicular volume < 4 ml, the hip-to-height ratio (HHR) was positively correlated with BSQ score (β=8.17, P<0.01). In boys with testicular volume ≥ 4 ml and nonfirst spermatorrhea, the HHR and SST were positively correlated with BSQ score (β=2.51, P=0.04; β=4.98, P<0.01). In boys with first spermatorrhea, weight was positively correlated with BSQ score (β=10.30, P<0.01). In girls with breast development < Tanner stage II, waist-to-height ratio (WHtR) was positively correlated with BSQ score (β=5.12, P<0.01); In girls with breast development ≥ Tanner stage II and nonmenarche, chest-to-sitting height ratio (CSHR) was positively correlated with BSQ score (β=10.82, P<0.01), and waist-to-hip ratio (WHR) was negatively correlated with BSQ score (β=-3.61, P=0.04). In girls with menarche, WHtR and sitting height-to-height ratio (SHHR) were positively correlated with BSQ score (β=6.09, P<0.01; β=2.05, P=0.02). Conclusion: The associations between body image dissatisfaction and anthropometric indices among Chinese children and adolescents at different developmental stages are different.